Hypothalamic Gliosis Is Associated With Multiple Cardiovascular Disease Risk Factors in the Framingham Heart Study - Justin Lo; Susan J. Melhorn; Sarah Kee; Kelsey L. W. Olerich; Alyssa Huang; Dabin Yeum; Alexa Beiser; Sudha Seshadri; Charles DeCarli; Ellen A. Schur (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Hypothalamic gliosis is mechanistically linked to obesity and insulin resistance in rodent models. We tested cross‐sectional associations between radiologic measures of hypothalamic gliosis in humans and clinically relevant cardiovascular disease risk factors, as well as prevalent coronary heart disease. Methods and Results Using brain magnetic resonance imaging from FHS (Framingham Heart Study) participants (N=867; mean age, 55 years; 55% women), T2‐signal intensities were extracted bilaterally from the region of interest in the mediobasal hypothalamus (MBH) and reference regions in the amygdala and putamen. T2‐signal ratios were created in which greater relative T2‐signal intensity suggests gliosis. The primary measure compared MBH with amygdala (MBH/amygdala). Outcomes were body mass index, high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol, fasting triglycerides, and the presence of hypertension (n=449), diabetes (n=66), metabolic syndrome (n=254), or coronary heart disease (n=25). Statistical testing was performed using linear or logistic regression. Greater MBH/amygdala T2‐signal ratios were associated with higher body mass index (P<0.001), higher fasting triglycerides (P<0.001), lower high‐density lipoprotein cholesterol (P=0.034), and presence of hypertension (P=0.0088), and the latter 2 were independent of body mass index. Findings for diabetes were mixed, whereas metabolic syndrome was strongly associated with greater MBH/amygdala T2‐signal ratios (P<0.001). T2‐signal ratios were not associated with prevalent coronary heart disease (all P>0.05), but CIs were wide. Conclusions Using a well‐established study of cardiovascular disease development, we found evidence linking hypothalamic gliosis to multiple cardiovascular disease risk factors, independent of adiposity. Our results highlight the need to consider central nervous system mechanisms to understand and improve cardiometabolic health.